Menyemai Cahaya, Menata Peradaban Islami di Desa Purnakarya, Kecamatan Tanralili, Kabupaten Maros: Sowing Light, Shaping an Islamic Civilization in Purnakarya Village, Tanralili District, Maros Regency - Sri Ujiana Putri (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2025)
In every journey, there are stories waiting to be preserved. In every act of service, there are lessons ready to be learned. Kuliah Kerja Nyata (KKN) is not merely an academic program, but a journey that teaches the meaning of togetherness, compassion, and social responsibility. Within a short period of time, students immerse themselves in community life, feel its pulse, and learn from the richness of local wisdom. KKN is a compulsory course that must be carried out by every university student. Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) holds KKN once a year, and in 2025 STIBA Makassar conducted the program in Tanralili District, covering 7 villages and 1 sub-district for a duration of 57 days, from February 26, 2025 to April 24, 2025. One of its goals is to train students in developing practical skills and experience in empowering communities. As a result, the KKN female students successfully implemented work programs focusing on religious development, including Silaturrahmi, Pesantren Kilat, teaching in schools, Taklim Fikih Muslimah, Arabic language instruction, Tebar Ifthar, and cupping therapy services.